Liberal politician, interventionist policymaker: Oswaldo Aranha’s Economic Thought - Salomão, Ivan Colangelo (Iberian Journal of the History of Economic Thought, 2021)
Oswaldo Aranha was one of the most famous and prestigious Brazilian politicians of the 20th century. Known for presiding the UN session when the State of Israel was created, Aranha had an important role in Brazilian politics during the first half of the century. Even though he held a bachelor’s degree in Law, Aranha had to deal with various economic issues along his political career. This paper aims to analyze his economic ideas, arguing that despite his liberal influences, he became an interventionist policymaker in Getúlio Vargas’s administrations. We argue that his experience as the Brazilian Ambassador in Washington played a central role in the changes of his ideological positions and economic ideas